DEVELOPMENT OF PREDICTION MODELS OF OIL & GAS PIPELINE SUBJECT TO CORROSION USING REGRESSION TECHNIQUES - ROSLI, MUHAMAD FADHLI (2020)
Pipeline condition deteriorates as it grew older. Various corrosion mechanisms have direct relation to pipeline deterioration, which ends with structural failure. I